IMPLEMENTASI MANAJEMEN SARANA PRASARANA DALAM UPAYA MENINGKATKAN MINAT CALON PESERTA DIDIK DI MA HARUN AL-RASYID BONTONOMPO KABUPATEN GOWA - Asmiani Nurul Adystia; Mardhiah, Mardhiah; Hamsiah Djafar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the management of facilities and infrastructure at MA Harun Al-Rasyid Bontonompo in increasing student interest, from a planning, implementation, and evaluation perspective. This study employed a qualitative phenomenological approach with descriptive methods. Data were obtained through observation, interviews, and documentation from primary sources (the Principal, teachers, administrative staff, students) as well as secondary sources. Data analysis techniques included data reduction, presentation, and conclusion drawing, with validity maintained through triangulation. The results indicate that the implementation of facilities and infrastructure management has been structured and contributed significantly to increasing student interest. First, planning was carried out collaboratively based on student needs, despite ongoing budget constraints. Second, implementation proceeded optimally through teamwork in maintaining clean and tidy facilities, effectively promoting the school. Third, evaluations were conducted regularly through inventory and observation for continuous improvement. Overall, this planned and measurable management has successfully strengthened the image of the madrasah and created a comfortable learning environment for students.